Thermal Testing of Titanium Implants and the Surrounding Ex-Vivo Tissue Irradiated With 9.3um CO2 Laser. Issue 5 (October 2019) - Froum, Scott H.; Cantor-Balan, Roni; Kerbage, Charles; Froum, Stuart J.
Abstract : Purpose: To measure the temperature rise and surface damage of titanium dental implants and the surrounding tissue in a pig jaw during 9.3-μm carbon dioxide (CO2 ) laser irradiation at various durations of time. Materials and Methods: Thermal analysis tests were performed on 12 implants with the same surface. Twelve implants mounted alone or in pig jaws were laser-irradiated with a 9.3-μm CO2 laser using 3 different power settings. The temperature of the implant body and the proximal tissues was measured with a J-Type Thermocouple after being laser-irradiated with 3 different power setting for 30, 60 seconds, and 2 minutes. Scanning electron microscope (SEM) and digital microscope images were also taken of the all the implants before and after laser irradiation to detect the presence or absence of surface damage. Results: Temperature analysis showed that in all cases the implant and the proximal tissue temperatures remained around the start temperatures of the implant and tissues with fluctuations of ±3°C but never reached the upper threshold of 44°C, the temperature at which thermal injury to bone has been reported. Digital and SEM images that were taken of the implants showed an absence of surface damage at the cutting speed of 20% (0.7 W); however, cutting speeds of 30% to 100% (1.0–4.2 W) did yield surface damage. Conclusions: Laser irradiation of titanium implant surfaces using a 9.3-μm carbon dioxide laser with an average power of 0.7 W showed no increase in thermal temperature of the implant body and tissue temperatures as well as no evidence of implant surface damage.